A Quantitative Analysis of Firewall Impact on Critical Data Communication - Minhaj Ahmad Khan (Journal of Basic & Applied Sciences, 2013)
Multimedia communication is considered to engulf the entire transmission taking place through internet. Most of the applications running on clients communicating through internet incorporate video or audio data transmission. Such transmission may however hinder the performance of other critical applications running on the network. For instance, the clients connecting to a database may suffer large delays if the network bandwidth is being utilized for multimedia communication. In this regards, a firewall may be used to block the non-critical and unnecessary communication. In this paper, we perform a quantitative analysis to record the impact of a firewall deployed in a network. We develop various network scenarios with voice and video data being transmitted in parallel with queries from a database client. As the database application is critical for its clients, the unnecessary communication causing the wastage of bandwidth is blocked through a firewall. We record the improvement in the performance of the database application due to the usage of firewall. We simulate all the scenarios using OPNET IT Guru v 9.1. Our results show that due to the blocking of video transmission, there is a significant improvement in performance of the database application. We also find that the use of a firewall has an overhead that depends mainly on the amount of communication taking place simultaneously and can also impact the performance of the critical application.